(3GdEYdGe aj ETGQGJ Cgd GdEdgGes - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3GdGeQ GdMce GdeQHhW s)
(3ChdgG (B:s
(3jHOC HHGH ai GdQDjI s
(3BNQgG (B:s
(3hbGd HYVge GdQLd YGWT GHOkG hbGd HYVge Gd QLd ef jfab hbGd HYVge GdQLd ef jfab Ydjg bGd LGeY gPg GdGTGQGJ QVi Gddg Yfg eG bjOJ ajgG GdG eG SeYJg ef bGFdg GdG ef PcQJ GSeg hGdMeO ddg hMedJgG eG jJGf hHVYI hSJhf cdeI hddg GdMeO hGdefI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B103s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs